Performance investigation of energy transport media as influenced by crop based properties - Ani, Farid Nasir (Universiti Teknologi Malaysia, 2005)
Todays concern of protecting the environment has encouraged the research and the use of environmental friendly products. This project initiates the experimental investigation of using palm based oil as hydraulic fluid. This research was aimed at obtaining a better understanding of short term performance and long term durability of palm based oil working as hydraulic fluid. A vane pump test rig was designed and built. The instantaneous data were recorded in a computer using an analog-to-digital data acquisition system. The rig was integrated with LabVIEW software version 6.1. Among the data stored are reservoir and return line temperatures, suction and delivery pressures, instantaneous flow rate, total flow, total running time and torque. Test rig performance running on palm oil was determined and monitored. In order to predict the oil performance in the test rig operation, bench tests were also conducted in evaluating the thermal and rheological performance of the oil. The bench tests gave useful insight to the performance of the actual test rig. Some improvement of the oil was made and tested on the hydraulic test rig. The results indicate that ageing process was significantly improved by the additived oil. The investigation also indicates that flow slip, viscous friction, and coulomb friction coefficients were affected by oil and hydraulic component conditions. Non-Newtonian behavior of the oil had been analyzed using five rheological models. It was found that Cross and Carreau rheological models provided best correlation coefficient (R2 > 0.999) to the oil under investigation. The palm oil had relatively strong shear thinning behavior with flow behavior index (n) lower than 0.8 compared to mineral hydraulic oil (n>0.9). However this effect was less pronounced at high temperatures. Modified power law and generalized models were proposed to study variation of Newtonian level of the oil with temperature and shear rate. Thermal stability of the oils was also investigated using thermogravimetry analysis (TGA). Based on thermodynamic activation energy (Ea), onset temperature and acid value, the recommended treat level for F10 additive is between 1.5% to 2% (wt/wt) while for L135 additive is 1.5% (wt/wt). In the aspect of tribology, more than 60% wear occurred during the first 500 hours of operation. In general, the results show that the additived palm oil is comparable if not better than the commercial biodegradable hydraulic fluid that is derived from rapeseed oil.